Impact Analysis of PT Fraud Cases. The Three Pillars of Sejahtera Food.Tbk and Efforts by Capital Market Regulators to Compensate Capital Market Investors' Losses - Delvina Koniardy; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Financial statements are important information needed by investors, creditors, analysts and certain parties which are used as a basis for investing in an asset. However, fraud is often found in financial reports. PT. Tiga Pilar Sejahtera Food Tbk is an example in cases of financial report manipulation practices. The method used in this research is descriptive, in which this research uses a type of research that produces descriptive data or results in the form of written or spoken words from the object of observation. The results of this study concluded that PT. Tiga Pilar Sejahtera Food Tbk has resulted in losses to investors and the OJK as a regulator has imposed administrative sanctions, suspended assets and revoked business licenses